Instalasi dan Implementasi Perangkat CCTV bagi Warga dan Karang Taruna Desa Cikedokan Cikarang Barat - Akmaludin, Akmaludin; Sihombing, Erene Gernaria; Rinawati, Rinawati; Dewi, Linda Sari; Arisawati, Ester (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
Cikedokan is a village located in the West Cikarang sub-district, Bekasi Regency, West Java Province. The residents and youth of Karang Taruna in Cikedokan Village certainly want to know and develop the application of technology to advance Cikedokan Village, so they need knowledge about CCTV installation. The problem faced in the Cikedokan Village environment is that there are no resident personnel and Youth Organizations in Cikedokan Village who are able to do so. We, from the Nusa Mandiri University Lecturers, provide counseling in the form of Community Service providing solutions to overcome the problems faced by residents and the Karang Taruna of Cikedokan Village to provide installation training for CCTV devices. We do this with the aim of providing full support to residents and youth organizations in mastering the devices used in CCTV installations optimally, so that this training activity is expected to be useful for implementing the use of CCTV for various purposes so that it can be implemented, especially in increasing citizen knowledge. and Karang Taruna of Cikedokan Village. The results of this Community Service activity provided an increase in understanding and mastery of CCTV camera installation as a basic step through the stages of the installation process and its application, in the Cikedokan Village environment, West Cikarang. The residents and Karang Taruna of Cikedokan Village hope that it will be necessary to hold it again to better understand and expedite the assembly of the CCTV camera installation.